2017
DOI: 10.21873/anticanres.11903
|View full text |Cite
|
Sign up to set email alerts
|

Critical Overview of HER2 Assessement in Bladder Cancer: What Is Missing for a Better Therapeutic Approach?

Abstract: Improved HER2 assessement is needed for urothelial carcinomas. HER2-IHC scored as 0-2 should be validated by and reclassified according to FISH analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Finally, in the meta-analysis literature we included, HER2 expression was measured by the IHC method only. It has been suggested that the results of IHC and fluorescence in situ hybridization (FISH) were not completely consistent when detecting HER2 expression in bladder cancer (52,53). A combination of FISH assays is needed for further research in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in the meta-analysis literature we included, HER2 expression was measured by the IHC method only. It has been suggested that the results of IHC and fluorescence in situ hybridization (FISH) were not completely consistent when detecting HER2 expression in bladder cancer (52,53). A combination of FISH assays is needed for further research in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In considering a different molecular target, HER-2 (EGFR2/ERBB2/NEU) has been found to be significantly overexpressed in canine InvUC samples when compared to non-neoplastic urothelium (79), as is the case in human InvUC (80,81). In two immunohistochemical studies HER-2 immunoreactivity was noted in 13 of 23 (56%) and in 14 of 23 (60.9%) cases of canine InvUC, respectively (79, 82).…”
Section: Other Molecular Featuresmentioning
confidence: 99%
“…Cox-2 is also overexpressed in more than 80% of human (Bourn et al 2019) and canine BC (Knapp et al 2014). HER-2 (EGFR2/ERBB2/NEU) has been found to be signi cantly overexpressed in canine invasive BC (Millanta et al 2018), as is the case in human invasive BC (Eriksson et al 2017;Cimpean et al 2017) when compared to non-neoplastic urothelium. The standard treatment options for invasive BC in humans and dogs are nearly similar and both species showed similar responses to treatments (Knapp et al 2019).…”
mentioning
confidence: 89%